OPTIMAL LINEAR COMBINED FILTERING OF RANDOM SEQUENCES BASED ON THE RECURSIVE LEAST SQUARES METHOD - V. M. Artemiev; A. O. Naumov; L. L. Kokhan (Informatika)
The problem of the synthesis of linear combined filter for the criterion of minimizing current losses on the basis of the recursive least squares method is being solved. This approach does not requirea priori knowledge of the statistical characteristics of impacts that is an advantage compared with the Kalman filter. A comparative evaluation of the filters’ accuracy is provided using the values of variances of the filtering errors.